A new methodology for evaluation and benchmarking of skin detector based on ai model using multi criteria analysis - Qahtan Majeed Yas (Tanjong Malim, 2018)
A new methodology for evaluation and benchmarking of skin detector based on ai model using multi criteria analysis by Qahtan Majeed Yas